Daya Saing Komoditas Lada Di Indonesia Tahun 2018-2022 - Riani, Novi (Margin: Jurnal Bisnis Islam dan Perbankan Syariah, 2023)
The development of Indonesia's pepper production with its total area, as well as pepper exports as seen from the export volume and export value, which fluctuate every year. The aim of this research is to determine the competitiveness of pepper commodities in Indonesia in 2018-2022 and to find out what influences the competitiveness of pepper commodities in Indonesia in 2018-2022. The types and sources of data used in this study are quantitative data types originating from secondary data. Based on the results of the research and discussion above, the conclusion in this study is that Indonesia's RCA value shows a value of more than one, which means that Indonesia has strong competitiveness in the pepper commodity so that Indonesia's competitiveness for pepper can be said to be above the world average. Factors (variables) that together significantly influence the competitiveness (RCA) of pepper in Indonesia are pepper production, pepper prices, world pepper prices and exchange rates. The factor (variable) that individually has a significant effect on the competitiveness (RCA) of pepper commodities in Indonesia is the exchange rate. The advice that can be given in this study is to increase the competitiveness of the pepper commodity in Indonesia, it is necessary to increase the quality and quantity of sales of pepper by developing and increasing exports of pepper in processed form, so as to increase the volume and value of pepper exports. To increase pepper production in Indonesia, several ways can be done, namely by providing training and guidance to farmers and the pepper processing industry, providing facilities, and increasing research related to pepper processing techniques and processes. Thus the pepper commodity can remain competitive in the international market.